Impaired Hepatocyte Regeneration in Acute Severe Hepatic Injury Enhances Effective Repopulation by Transplanted Hepatocytes - Chun-Hsien Yu; Hui-Ling Chen; Ya-Hui Chen; Ming-Fu Chang; Chin-Sung Chien; Mei-Hwei Chang M.D. (Cell Transplantation, 2009)
Efficient repopulation by transplanted hepatocytes in the severely injured liver is essential for their clinical application in the treatment of acute hepatic failure. We studied here whether and how the transplanted hepatocytes are able to efficiently repopulate the toxin-induced acute injured liver. Male dipeptidyl peptidase IV-deficient F344 rats were randomized to receive retrorsine plus D-galactosamine (R+D-gal) treatment or D-galactosamine-alone (D-gal) to induce acute hepatic injury, and retrorsine-alone. In these models, retrorsine was used to inhibit the proliferation of endogenous hepatocytes while D-galactosamine induced acute hepatocyte damage. Wild-type hepatocytes (1 × 10 7 /ml) were transplanted intraportally 24 h after D-galactosamine or saline injection. The kinetics of proliferation and repopulation of transplanted cells and the kinetics of cytokine response, hepatic stellate cell (HSC) activation, and matrix metalloproteinase (MMP2) expression were analyzed. We observed that early entry of transplanted hepatocytes into the hepatic plates and massive repopulation of the liver by transplanted hepatocytes occurred in acute hepatic injury induced by R+D-gal treatment but not by D-gal-alone or retrorsine-alone. The expressions of transforming growth factor-α and hepatocyte growth factor genes in the R+D-gal injured liver were significantly upregulated and prolonged up to 4 weeks after hepatocyte transplantation. The expression kinetics were parallel with the efficient proliferation and repopulation of transplanted hepatocytes. HSC was activated rapidly, markedly, and prolongedly up to 4 weeks after hepatocyte transplantation, when the expression of HGF gene and repopulation of transplanted hepatocytes were reduced afterward. Furthermore, the expression kinetics of MMP2 and its specific distribution in the host areas surrounding the expanding clusters of transplanted hepatocytes are consistent with those of activated HSC. Impaired hepatocyte regeneration after acute severe hepatic injury may initiate serial compensatory repair mechanisms that facilitate the extensive repopulation by transplanted hepatocytes that enter early the hepatic plates.